Academic Leadership of Private School Director in Sisaket Province - Phokrasang, Sakuna; Wattanasak, Krisada; Romsri, Suwattanapong (Journal for Developing the Social and Community, 2022)
This research purposed to study and compare the opinions of the School Administrative Committee of private schools in Sisaket Province on academic leadership of private schools director in Sisaket Province. Classified by position, age and educational level. The population is the school administration committee of private schools in Sisaket Province, Academic Year 2020 of 87 people. A constructed 5-level rating scale questionnaire and the reliability of 0.87 . Data analysis to analyzed by frequency, percentage, mean, standard deviation, and the statistics used for hypothesis testing were t-test and F-test. The results of the research were as follew : 1. Opinions of the School Administrative Committee of Private Schools in Sisaket Province on academic leadership of private schools director in Sisaket Province Overall, it’s at a high level. When considering each aspect, it was found that Academic Leadership of Private School Director at a high level in every item. The averages were sorted from highest to lowest : the obligation basic knowledge Skills required in management. 2. Opinion of the School Administrative Committee of Private Schools in Sisaket Province on academic leadership of the director of private schools in Sisaket Province classified by status overall and each aspect was not different, classified by age, overall and each aspect was not different. Classified by educational level Overall and each aspect is no different.